Regulatory mechanism analysis of signal transduction genes during rapeseed (Brassica napus L.) germination under aluminum stress using WGCNA combination with QTL - Li, Chenyang; Wang, Ruili; Li, Jiana; Zhou, Qingyuan; Cui, Cui (Frontiers in Plant Science, 2025)
As soil becomes more acidic, aluminum toxicity has emerged as a key issue impacting seed germination and crop productivity in such environments. Therefore, it is urgent to investigate the mechanism of the influence of aluminum stress on germination. In this study, we focused on one of the major bioenergy crops—rapeseed. Seeds of aluminum-sensitive (S) and aluminum-resistant (R) lines screened from the recombinant inbred lines (RILs) population of rapeseed were treated with 80 µg·ml-1 AlCl3 (ST, RT). Purified water served as the control (SC, RC). On the 3rd, 5th, and 7th day after treatment, the root tissue was collected for transcriptome sequencing. Utilizing MapMan software, the genes showing differential expression in S and R lines were assigned to the aluminum stress signaling pathway, resulting in the identification of 1036 genes. By weighted gene co-expression network analysis (WGCNA), five co-expressed gene modules associated with aluminum stress were discovered. A total of 332 candidate genes were screened by combining the genes related to aluminum stress signal transduction pathways with the module hub genes. Among them, 26 key genes were located in quantitative trait loci (QTL) with confidence intervals for germination-related traits of rapeseed under aluminum stress, and primarily distributed in 11 QTL regions, such as qRDW-A09-1, qRDW-A10-1 and qRGV-A01-2, they were associated with relative root length (RRL), relative root dry weight (RDW), relative germination vigor (RGV) and relative bud length (RBL). The roles included transcription regulation, stress protein production, redox processes, hormone signaling, cell wall alteration, and calcium-based signal transmission. Compared with the R line, the S line exhibited quicker and stronger activation of genes related to aluminum stress signal transduction, suggesting that the S line was more responsive to aluminum stress. This research offers an empirical basis for identifying aluminum-resistant rapeseed varieties and investigating the molecular regulation of aluminum tolerance during germination.